Pengaruh Literasi Digital Terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar Pada Era Transformasi Pendidikan - Siti Asiah; Rahmawati Hidayah; Tutik Handayani (Jurnal Pacu Pendidikan Dasar, 2025)
This study aims to explore the influence of digital literacy on elementary school students’ critical thinking skills within the context of educational transformation. This transformation requires students not only to master academic content but also to evaluate, analyze, and apply information critically in digital environments. The study employs a quantitative approach with a descriptive correlational design to identify the relationship between digital literacy and critical thinking skills. The sample consists of 4th to 6th grade students from several elementary schools in Indonesia. Data were collected through digital literacy questionnaires, critical thinking tests, and observations of technology-based learning. The analysis was conducted using descriptive and inferential statistics to measure the levels of both variables and their relationship. The results indicate that digital literacy significantly contributes to the improvement of students’ critical thinking skills. Technology-based learning, such as digital libraries, microlearning, and the ARIAS model, encourages information evaluation, logical argument construction, and collaboration. The findings also highlight the role of teachers as facilitators in guiding the use of technology and stimulating critical reflection. Integrating digital literacy into the curriculum is a key strategy for developing 21st-century skills.